ChASTOTA PERELOMOV PROKSIMAL'NOGO OTDELA BEDRA I DISTAL'NOGO OTDELA PREDPLECh'Ya SREDI NASELENIYa IRKUTSKOY OBLASTI - L. V. Men'shikova; A. A. Dzizinskiy; N. A. Khramtsova (Научно-практическая ревматология)
Aim: Study of the prevalence of basic osteoporotic fractures in the proximal femoral bone and distal forearm in persons aged more than 50 in Irkutsk region. Materialas and methods: Retrospective epidemiologic study aimed the prevalence of proximal femural and distal forearm fractures in patients aged more than 50 for 1992-1997 was carried out in 3 cities of Irkutsk region. Medical documentation of traumatological services and stations, medical care services and boarding houses was analyzed. Results: Femoral fractures prevalence in males was between 33.4 and 75/100,000 man/years of observation, being in median 61.7/100,000. Among females it fluctuated between 72.9 and 110.7, in median - 100.9/100,000. M:F was 1:2.4. Prevalence of femoral fractures increased at the age of 70 and more, reaching maximum after 80 - that is 577.6 in females and 259.5 in males/100,000. Distal forearm fractures prevailed in males by 2.4 times and by 7 times in females as compared with hip fractures. Forearm fractures prevalence was averagely 489.5/100,000 in the region (720.2 in females and 146.5 in males, p<0.0001). All age groups demonstrated reliably higher fracture prevalence in females. Increase of fracture prevalence in both sexes was noted after 65 years with decrease after 80 years.